The prognostic value of admission D-dimer level in patients with cardiogenic shock after acute myocardial infarction - Jiang, Yi; Zhu, Yuansong; Xiang, Zhenxian; Sasmita, Bryan Richard; Wang, Yaxin; Ming, Gong; Chen, Siyu; Luo, Suxin; Huang, Bi (Frontiers in Cardiovascular Medicine, 2023)
Background Shock is associated with the activation of the coagulation and fibrinolytic system, and D-dimer is the degradation product of cross-linked fibrin. However, the prognostic value of D-dimer in patients with cardiogenic shock (CS) after acute myocardial infarction (AMI) remains unclear. Methods We retrospectively analyzed the data of consecutive patients with CS complicating AMI. The primary endpoint was 30-day mortality and the secondary endpoint was the major adverse cardiovascular events (MACEs) including 30-day all-cause mortality, ventricular tachycardia/ventricular fibrillation, atrioventricular block, gastrointestinal hemorrhage, and non-fatal stroke. Restricted cubic spline (RCS) analyses were performed to assess the association between admission D-dimer and outcomes. A multivariable Cox regression model was performed to identify independent risk factors. The risk predictive potency with D-dimer added to the traditional risk scores was evaluated by C-statistics and the net reclassification index. Results Among 218 patients with CS complicating AMI, those who died during the 30-day follow-up presented with worse baseline characteristics and laboratory test results, including a higher level of D-dimer. According to the X-tile program result, the continuous plasma D-dimer level was divided into three gradients. The 30-day all-cause mortality in patients with low, medium, and high levels of D-dimer were 22.4, 53.3, and 86.2%, respectively (p < 0.001 for all). The 30-day incidence of MACEs was 46.3, 77.0, and 89.7%, respectively (p < 0.001). In the multivariable Cox regression model, the trilogy of D-dimer level was an independent risk predictor for 30-day mortality (median D-dimer cohort: HR 1.768, 95% CI 0.982–3.183, p = 0.057; high D-dimer cohort: HR 2.602, 95% CI 1.310–5.168, p = 0.006), a similar result was observed in secondary endpoint events (median D-dimer cohort: HR 2.012, 95% CI 1.329–3.044, p = 0.001; high D-dimer cohort: HR 2.543, 95% CI 1.452–4.453, p = 0.001). The RCS analyses suggested non-linear associations of D-dimer with 30-day mortality. The enrollment of D-dimer improved risk discrimination for all-cause death when combined with the traditional CardShock score (C-index: 0.741 vs. 0.756, pdifference = 0.004) and the IABP-SHOCK II score (C-index: 0.732 vs. 0.754, pdifference = 0.006), and the GRACE score (C-index: 0.679 vs. 0.715, pdifference < 0.001). Similar results were acquired after logarithmic transformed D-dimer was included in the risk score. The improvements in reclassification which were calculated as additional net reclassification index were 7.5, 8.6, and 12.8%, respectively. Conclusion Admission D-dimer level was independently associated with the short-term outcome in patients with CS complicating AMI and addition of D-dimer brought incremental risk prediction value to traditional risk prediction scores.